Factors Affecting the Learning Listening English - Kurniawati, Dewi (English Education: Jurnal Tadris Bahasa Inggris, 2019)
The main aim of this research is to examine where the difficulties are from internal factors and external factors. The methodological approach taken in this research is descriptive qualitative, in other words, in this study the collection of data contained in the form of reports and description. Of the study population, 40 students, 33 were female and 7 male returned the questionnaires. From the results of this research found that the factors causing difficulty in listening to students are; declining health condition or illness, the elusive material, a lack of support, lack of training to improve English listening whether with their classmates or with native speakers.